Strategies for Preventing Disease Transmission at Early Childhood Education Institutions - Jauhari Jauhari (International Journal of Emerging Issues in Early Childhood Education, 2020)
Early childhood education institutions with a lack of health standards can be a medium for disease transmission. This transmission leads to a decline in health status and the level of children's development. Preschool children often suffer from several infectious diseases such as chickenpox, diphtheria, measles, mumps, hepatitis B, influenza, pulmonary tuberculosis, impetigo, and diarrhea. These diseases can be transmitted through direct or indirect contact such as respiratory tract, digestion, and skin. Disease transmission can occur during interactions between children and children, children and teachers, and children and the environment around the school. The risk of disease transmission can be reduced by implementing prevention strategies for disease transmission, that is, by creating a healthy environment of the educational institution, keeping hands clean, providing handwashing facilities, implementing cough ethics, and increasing the role of teachers and parents to establish children's clean and healthy living behavior. These strategies can work well if they are supported and carried out by the manager, teachers, children, educational personnel, and parents. The strategies are expected to improve the health status of children, so they can achieve growth and development by their stages.